The Comparison of the Video Game Development Process with and without the Use of Artificial Intelligence - Ivanichenko, Anton; Šedivá, Zuzana, 1961-; Vencovský, Filip; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
The main goal of this bachelor thesis is to compare the processes of video game development with and without the use of artificial intelligence. The output of this work is a comparative analysis of two game prototypes: manually developed and artificially developed. The analysis focuses on three factors: time costs, financial costs, and overall quality of the prototypes. This work also inspects several other topics, such as the definition of a video game, roles in the game development team, and components.
Vedoucí práce: Zuzana Šedivá
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses